MRI characteristics of adductor longus lesions in professional football players and prognostic factors for return to play. Issue 108 (November 2018) - Pezzotta, G.; Pecorelli, A.; Querques, G.; Biancardi, S.; Morzenti, C.; Sironi, S.
Abstract: Purpose: To correctly define through Magnetic Resonance Imaging (MRI), diagnosis, staging and prognosis of the adductor longus (AL) acute lesions and to identify a correlation between Return to Play (RTP) and sport-related injury predisposing conditions and complications. Materials and methods: Twenty professional football players with acute groin pain and clinical suspicion of AL injury subsequent to sport's activity were evaluated. MRI examinations were performed by one and reviewed by other two radiologists with more than 10 years of experience. Lesions were stratified according to both Munich consensus statement and British Athletics Muscle Injury Classification (BAMIC). Patients were monitored until clinical recovery occurred. Results: According to the Munich consensus statement, 75% of lesions were defined as type 3 and 25%as type 4; while according to the BAMIC, 45% were considered as Grade 1, 20% as Grade 2, 10% as Grade 3, and 25% as Grade 4. RTP was 1–2 weeks for minor lesions (45%), 4–6 weeks for moderate lesions (30%), and more than 6 weeks for complete lesions (25%). Both BAMIC and Munich consensus significantly correlated with RTP (R = 0.958 and 0.974, respectively). The extent of gap was the only independent prognosticator of RTP always present in all three different models of multivariate analysis (p < 0.006, p < 0.002, and p < 0.001, respectively). Conclusions: MRI represents the gold standard imaging technique for the evaluation of AL due to its ability not only to recognize but also to classify acute lesions and define patient's prognosis. MRI is also useful to detect potential predisposing conditions and complications, which may correlate with RTP.